2022
DOI: 10.2174/1573399817666210614113827
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness and Type 1 Diabetes: The Current State of Knowledge

Abstract: : The most common cause of mortality among people with type 1 diabetes is cardiovascular diseases. Arterial stiffness allows predicting cardiovascular complications, cardiovascular mortality, and all-cause mortality. There are different ways to measure arterial stiffness; the gold standard is pulse wave velocity. Arterial stiffness is increased in people with type 1 diabetes compared to healthy controls. It increases with age and duration of type 1 diabetes. Arterial stiffness among people with type 1 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…These findings suggested that their mechanism is determined mainly by insulin resistance due to endothelial dysfunction, an abnormal insulin vasodilating effect mediated by endothelium-derived nitric oxide [ 15 , 16 ]. It has been reported from cohort and transversal studies that HbA1c is associated and correlated with arterial stiffness assessed by PWV [ 17 , 18 , 19 ]. However, according to our research, these studies do not explore the mediator effect of insulin resistance (IR) on the association between HbA1c and PWV.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that their mechanism is determined mainly by insulin resistance due to endothelial dysfunction, an abnormal insulin vasodilating effect mediated by endothelium-derived nitric oxide [ 15 , 16 ]. It has been reported from cohort and transversal studies that HbA1c is associated and correlated with arterial stiffness assessed by PWV [ 17 , 18 , 19 ]. However, according to our research, these studies do not explore the mediator effect of insulin resistance (IR) on the association between HbA1c and PWV.…”
Section: Introductionmentioning
confidence: 99%
“…Another important finding was that patients with recently diagnosed T2DM and no cardiovascular risk factors had higher AS compared with healthy controls and, therefore, probably had premature vascular aging [ 30 ]. Some papers have also emphasized the importance of the early diagnosis of AS in T1DM and its clinical value in the prevention of CVD [ 31 ].…”
Section: Arterial Stiffness In Patients With Diabetesmentioning
confidence: 99%